Selective Adsorption of Fe (III) Using Calcium Alginate-Polyacrylamide/Titanium Dioxide Nanocomposites Prepared by Gamma Irradiation (Journal of Nuclear Technology in Applied Science, 2019)
Calcium alginate-polyacrylamide/titanium dioxide (CA-PAM/TiO2) nanocomposite biofilms were prepared by solution casting followed by gamma irradiation as initiator. N,N’ Methylene bis acrylamide (MBAM) and CaCl2 were used as covalent and ionic crosslinker, respectively. Characterization of the prepared films was performed by XRD and SEM. Adsorption of Fe (III) ions was carried out by batch experiment under varying operating conditions such as, TiO2 content, pH, time, initial metal concentration, temperature and number of adsorption cycles in order to optimize the adsorption conditions for selective removal of Fe (III) from aqueous medium. Atomic absorption spectrophotometer was used to determine the adsorption behavior. Thermodynamic studies of Fe (III) adsorption were also evaluated and indicated that adsorption is chemical and endothermic in nature. Selective adsorption of Fe (III) was studied in the presence of Co (II) and Cu (II) ions as interfering ions. It was found that the selectivity coefficient of the CA-PAM/TiO2 for Fe(III) was 55 and 220 toward Cu (II) and Co (II), respectively. Such values are much higher than that of CA-PAM of composition 50/50 wt% without TiO2 nanoparticle which was 13.3 and 40 also toward Cu (II) and Co (II), respectively. It is concluded that such prepared materials are of interest for practical uses in the removal of Fe (III) from waste water
Keywords: Calcium Alginate Polyacrylamide; Nanocomposite; Titanium Dioxide; Adsorption; Gamma Radiation